PENGARUH KONFIGURASI TULANGAN SENGKANG TERHADAP KAPASITAS GESER DAN POLA KEHANCURAN KOLOM YANG DIBEBANI TEKAN AKSIAL - Mulyadi Mulyadi; Abdullah Abdullah; Surya Bermansyah (Universitas Bengkulu, 2019)
The study of bearing capacity and buckling behavior of reinforced foamed concrete column under compressive load.The aim of this research is for knowing the bearing capacity and buckling behavior of reinforced foamed concrete column. This research can be used as the base for precast column of reinforced foamed concrete in non engineered building.The samples for the reinforced foamed concrete column have, w/c : 0.5 ; SG: 1.2, and 0.5% in weight percentage . the control sample is a 15x30 cm cylinder. The column is 200 cm inheight.RFC2510 with cross section 25 x 25 has 4?10 mm main bars, and ?8-100 for stirrups. RFC3010 with cross section 30 x 30 has 4?10 mm main bars, and ?8-100 for stirrups. RFC3012 with cross section 30 x 30 has 4?12 mm main bars, and ?8-100 for stirrups. RFC2510-75 with cross section 25 x 25 has 4?10 mm main bars, and ?8-75 for stirrups.The type of load given is the axial load. In this research the average compressive strength is (f’c) 100.038 kg/cm2, the modulus of elasticity (Ec) is 29793.069 kg/cm2, and the average tensile strength (ft) is 9.572 kg/cm2.The capacity of axial load for each column RFC2510, RFC3010, RFC3012, RFC2510-75, is 49.990ton, 70.310 ton, 58.570 ton, and 51.910 ton respectively. The increase of axial load capacity is influenced by dimension and the distance of stirrups in the column sample. However in this research the using of the bigger bar diameter does not influence the axial load to the column sample. The ratio from the lab test to the theory one is less than 1. The suitable factor reduction for reinforced foamed concrete is 0.61